Continuous light at fixed daily light integral enhances lettuce growth due to improved light interception and light use efficiency - Núñez Ocaña, Diego; Esmaeli Sooderjani, Homa; Kusuma, Paul; Marcelis, Leo F. M.; Heuvelink, Ep (Frontiers in Plant Science, 2026)
Vertical farming (VF) allows precise control of growth conditions, but its high energy demand underscores the need to improve light-use efficiency. This study examined how continuous lighting (CL) affected the growth, morphology, and carbohydrate content of lettuce cultivars ‘Jagger’ and ‘Danstar,’ compared with the 18-hour photoperiod at the same daily light integral. The study also modelled the influence of photon efficacy of the LEDs under both lighting regimes on energy use and energy-use efficiency (EUE). Under CL, leaf area growth increased total light interception by 10% in ‘Jagger’, whereas in ‘Danstar’ it remained similar to the 18-hour photoperiod. Carbohydrate metabolism shifted, with sucrose decreasing and starch accumulating under CL, while other sugars remained unchanged. CL improved the use efficiency of intercepted light (LUE) by 7 to 11% relative to the 18-hour photoperiod. Consequently, fresh and dry mass increased by 23% in ‘Jagger’ and by 6% and 14% in ‘Danstar,’ respectively. Assuming the same photon efficacy of the LEDs, CL required the same energy input as the 18-hour photoperiod; however, due to the growth enhancement under CL, it resulted in a 16 to 18% higher EUE. Visual quality was unaffected in both cultivars, with no signs of tip-burn or bolting. These findings indicate that CL can simultaneously improve lettuce growth and energy use efficiency, offering a promising strategy to reduce energy costs and lighting investment in vertical farming.